Student Educational Resilience While Online Studying During the Covid-19 Period - Linda Yarni (Studies in Learning and Teaching, 2023)
Covid-19 has caused changes in education aspect so that it is forced to learn online. This condition has made the world of Education in shock that has caused stress on students who are conducting online learning when they don't have the resilience to help themselves. This research is aimed at identifying the extent of educational resilience of students when they are conducting online learning during covid-19 as well as comparing the extent of educational resilience of man and woman students. This research employed a descriptive comparative quantitative approach. 807 Junior high school and senior high school students in Bukittinggi West Sumatra province were the respondents in this study. The result of this research has shown that the extent of educational resilience of students in online study has been in the high category with 89.10% (score 51-150). The comparative T-Test have shown that there was no distinction inside the educational resilience level of male and female students with the sig. 2 tailed higher than 0.05.